Taxing freedom in Thessalian manumission inscriptions - Zelnick-Abramovitz, Rachel. (Mnemosyne, Supplements, 2013)
In Taxing Freedom Rachel Zelnick-Abramovitz examines manumission inscriptions from Hellenistic and Roman Thessaly, which record payments made to the poleis by manumitted slaves. In this original study the author explores the purpose of and the motivation behind these payments, apparently exacted as a federal impost, and places them in a wider historical and economic context. Based on a close examination of the epigraphic and literary evidence, Taxing Freedom offers important insights into the nature and extent of slavery and manumission in Hellenistic and Roman Thessaly, the Thessalian fiscal machinery, and the ways by which Thessalian poleis intervened in the economic life of their citizens to secure revenues.